The financial burden of chronic wounds in primary care: A real-world data analysis on cost and prevalence - Miguel Ángel Díaz-Herrera; Mónica González-Durán; Francisco Javier Rodríguez-Martínez; Gema Tujillo-Flores; Nuria Tuset-Mateu; Jose Verdú-Soriano; Vicente Gea-Caballero; Albert Sanllorente-Melenchón; Jesús Almeda-Ortega; Oriol Cunillera-Puértolas; Mateo Acedo-Anta; José Ramón Martínez-Riera (International Journal of Nursing Studies Advances)
Background: Chronic wounds place a substantial clinical and economic burden on health systems and significantly reduce the quality of life of those affected. However, there are no large-scale economic evaluations to assess costs based on data in a real-world environment. Objective: We aimed to analyse the costs of managing patients with chronic wounds (pressure injuries, ulcers of venous aetiology, ulcers of arterial aetiology, diabetes-related foot ulcers, and lower-limb ulcers of other aetiologies) in primary care in the southern area of Barcelona, Spain, through a 3-year real-world data analysis. Methods: The direct costs associated with specific treatment materials and primary care consultations were analysed using the electronic clinical records and financial management data of 54 primary care centres managed by the Catalan Institute of Health, which served a population ranging from 890,152 in 2015 to 939,747 in 2017. Results: Between 2015 and 2017, total expenditure was estimated at € 34,991,854 (Euros) (USD 39,548,000 -United States Dollars-). The cost of the specific treatment materials was € 8,455,787 (USD 9,555,885), with an annual average of € 2,818,596 (USD 3,185,295) and an increase of 18.5 % over the period. The cost of the consultations for chronic wound management was € 26,536,067 (USD 29,988,409). The cumulative annual prevalence of chronic wounds per 10,000 inhabitants was 86.70‱ in 2015, 88.03‱ in 2016 and 88.7‱ in 2017. Pressure injuries accounted for 46.39 % to 42.86 % of all chronic wounds. The direct extrapolation of chronic wounds costs to the total population of Spain was € 1,763,037,849 (USD 1,993,409,074) (mean annual average € 587,679,283 -USD 664,136,358-) during the study period, with a prevalence of 388,777 and an estimated peak of 413,897 in 2017. Conclusion: We found that chronic wounds have a significant economic impact and should be considered in the planning and management of healthcare resources to ensure adequate and sustainable primary care services. Tweetable abstract: Chronic wounds represent a significant clinical and economic burden in medical devices and consultations, costing 34.99 million euros over three years. Effective planning is essential for the sustainability of primary care services